Greener ullmann-type coupling of aryl halides for preparing biaryls using reusable Pd/ZrO2 catalyst - Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Synthetic Communications, 2011)
Biaryls with excellent yields can be prepared by the Ullmann-type coupling of aryl halides in the presence of potassium carbonate (as a base) and dimethylformamide (as a solvent), at 140 degrees C, using a reusable Pd (2.5wt%)/ZrO2 catalyst. The product yield of 4-iodoanisole coupling is strongly influenced by the catalyst preparation method, solvent, and base.
Keywords: Aryl halides; Biaryls; Pd; Ullmann coupling reaction; ZrO2